2021
DOI: 10.1007/s40271-021-00535-x
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Discontinuity in Cancer Care Trajectories: Patients’ Solutions

Abstract: Introduction Patients with cancer require specialized care from different care providers, challenging continuity of care in terms of information, relationships, and/or management. The recognition of discontinuity of care has led to different initiatives by the healthcare system over the years. Yet, making use of the theory on boundary objects and brokers, this research explores the active role of patients themselves in resolving discontinuity along their care trajectories. Methods Semi-structured interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Receiving conflicting information from different care providers tend to result in major uncertainty. A recent study showed that most cancer patients endeavor to establish a continuity of care and strive for a more active role in their treatment journey 51 …”
Section: Discussionmentioning
confidence: 99%
“…Receiving conflicting information from different care providers tend to result in major uncertainty. A recent study showed that most cancer patients endeavor to establish a continuity of care and strive for a more active role in their treatment journey 51 …”
Section: Discussionmentioning
confidence: 99%
“…When translated to research, this requires, for instance, research designs with hybrid and dynamic self-identifications (e.g., Meijer, 2011 andAzevedo andMann, 2021). In parallel, various person-oriented and person-centred approaches are emerging, that move beyond studying differences between groups of categorised individuals (e.g., "minorities" and "STEM-interested students") towards studying individual learners' experiencing, engaging, and gradually defining and developing themselves from the learners' own perspective Bakker, 2019 andVermond et al, 2022).…”
Section: Coinciding Societal Developmentsmentioning
confidence: 99%
“…The advent of internet enabled wider sharing of knowledge (e.g., via Wikipedia, YouTube, and ResearchGate), including previously unrepresented perspectives (Lankshear, 2003). Moreover, with work and society becoming more dynamic and less predictable (the pandemic being a prime example), interorganisational, intercultural, and interdisciplinary efforts are increasingly considered necessary to address the bigger issues (e.g., related to economy, climate, healthcare, and racism) that are at stake Bakker, 2011 andVermond et al, 2022). According to both politicians and scholars, this entails that aside from basic and job-specific skills, additional skills, referred to as transferrable skills, lifelong learning competences and, increasingly, as 21 st century skills, should become part of educational curricula.…”
Section: Coinciding Societal Developmentsmentioning
confidence: 99%